Response to ‘Hypnotic discontinuation is not synonymous with successful deprescribing: A Taiwan perspective’ - Kazuhiro Kurihara; Ko Sugiura; Akiyoshi Shimura; Kentaro Matsui; Shunsuke Takagi; Yuichi Inoue; Yoshikazu Takaesu (Psychiatry and Clinical Neurosciences, 2026)
This article is a response to ‘Hypnotic discontinuation is not synonymous with successful deprescribing: A Taiwan perspective’.